Efisiensi Pembelajaran Kelas Model Daring: 10.58569/jies.v2i1.724 - Riyanto, Agus; Supiharti (Pascasarjana Universitas Islam Jakarta, 2023)
The purpose of this article is to describe the effectiveness of online learning. Qualitative research is research that is detailed, in-depth, descriptive and produces data from interviews with people observed. These qualitative research methods, such as in-depth interviews, are used to understand the behavior of subjects or subjects. Due to the online nature of this research, interviews were conducted in the form of online interviews using the WhatsApp application. The primary data source is grade VI B students of SDN 1 Lemahtamba, Panguragan, Cirebon Regency totaling 31 people, while the secondary data source is library materials, books, and journals related to this study. The results of a survey of a large number of students showed that as many as 21 students thought they supported online learning. The rest are not supportive because their home environment is not yet supportive. From the discussion above, it can be said that online Indonesian learning is very effective. This can be seen from the achievement of the goal of language learning, namely improving Indonesian language skills.